Damage Prediction of Pre-cracked High-Pressure Pipelines. Issue 1 (1st August 2022) - Kundu, B; Ghosh, S; Ghosh, D; Saha, K; Chatterjee, I; Ghosh, S
Abstract: Due to the increasing need to transport fluids, the use of industrial pipes and their sustainability is a crucial aspect to address. The motive of this work is to predict the behaviour of a pre-cracked pipeline under internal and external pressure using Finite element simulation. An intermediate range of pressure conditions has been selected to analyse the dispersal of normalized stress intensity factor along a semi elliptical crack front for a predefined crack geometry. This work also presents a comparative study of various piping material behaviour to address a relatively better choice for industrial use. Among the various alloys considered in the analysis Inconel 625 was found to be most appropriate for the pressure range.